Problems of modern age global character –environmental protection and providing an investment in terms of economic crisis - Knežević, Snežana; Bilić, Marijan; Babić, Željko (Hotel and Tourism Management, 2013)
Degradation of enviroment represents a global problem, and its moving with an unpresidented pace. Due to human activities, during second half of the twentieth century, Earths ecosystem suffered transformation faster than any period in the worlds history. The increasing exploitation of natural resources, extinction of animal species and air pollution have led to the development of different ways with which different institutions, financial, private and government, face environmental problems. Today, it imposes an action, both contractual and cooperative from the representatives of public sector and owners of capital in the private sector in order to find the best possible solutions that will allow you to protect natural resources and environment. Every sector must unite their efforts – none can work isolatied. Obtaining capital for environmental protection is of general importance. Special importance should be given to financing ecoinnovation. Corporate social responsibility in protecting the environment should become an integral element of the strategy of companies and financial institutions. The question is whether it is possible to be both profit-oriented and environmentally responsible business? This review, which is located within a wide range of literature, focuses on key legal and financial aspects of environmental protection, with special reference to the limitations imposed by the current economic crisis. The purpose of this research is to present a relatively complete theoretical and practical system of both legal and financial problems concerning effective environmental protection. So far, the treated material was not sufficiently investigated in the practice of environmental management, finance and regulative framework, as one integral problem. The research method was applied to case studies of adequate sample units that make up for the various relevant institutions and the analytical method. Considering the research results it was concluded that the studied subject should be given greater attention by using the concept of this works author. It is proposed that ecological rhetoric should be transformed into concrete action, both in the legal domain, and in the sphere of financing environmental projects which together lead towards successful implementation of sustainable development.